Rancang Bangun Pengelolaan Dan Penggunaan Dana Desa Sistem Terpadu Dengan Metode Berorientasi Objek - Rasminto, Hendri; Siswanto, Siswanto; Danang, Danang (Universitas Diponegoro, 2019)
The Village Fund Budget is a revenue-sharing fund between the District and Village Governments for the welfare of the community. The budget obtained is managed by the village government for community development and welfare. Budget management by the Village Government has been regulated in the Semarang Regent Regulation Number 8 of 2016 concerning Village Financial Management that that Changes to the Village Revenue and Expenditure Budget are stipulated by Village Regulations. Budgeting that has to create a new form in Microsoft Excel will increase the length of work time and must understand excel logic. The absence of databases and security systems that are not yet available is a balance between the need for an information system for managing village expenditure expenditure budgets that will make time more effective in budgeting. This information system uses Visual Basic 6.0 with the MySQL database. The research method used is R & D which was developed by Borg and Gall (1983) through the following stages: Research and information collecting, Planning, Develop prelminary form of product, Prelminary field testing, Main product revision, Main field testing. Designing a system that will produce a prototype product that will be tested by internal and external experts who will assess the design is valid or not. If the design is valid, it will produce a Accounting Information System prototype product of the Village Revenue and Expenditure Management (APBDes) that can be used, but if the product is not valid, it will be repaired according to expert instructions until the product is declared valid and usable. After being declared valid by the expert, it will produce a prototype product that can be used.Â The purpose of the village income and expenditure budget management information system in the Kaliwungu village is expected to be able to assist in the preparation of village income and expenditure budgets so that the time needed to prepare the report is quite effective and not too late. With the distribution of access rights and security systems, the information system for managing village income and expenditure budgets is expected to be safer